Internalisasi Pendidikan Ekonomi pada Kelompok Petani Semangka Margo Tani: Studi Kasus Pada Kelompok Petani Semangka - Ika Nur Khomariyah; Sunaryanto Sunaryanto; Cipto Wardoyo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: A qualitative descriptive study was used for the process of internalizing palawija farmers to watermelon farmers in Wotgalih village, Yosowilangun sub-district, Lumajang regency. Based on the existing phenomena, the impact arising from the internalization process can be seen from the realm of economic education, especially non-formal education. Data and data sources were collected based on observations and interviews with several informants who lived in the Wotgalih Yosowilangun area. The results of the analysis of data collected from the management and members of the Margo Tani group are twofold: first, the process of internalization of palawija farmers and watermelon farmers together through three things, namely learning while working, learning by word of mouth and learning while practicing. The difference is among the three of them on palawija farmers, that is, palawija farmers' profession is obtained from generation to generation from the family. Unlike the farming of watermelons obtained through these three things without having to pay personal expenses. Second, the Impact of Internalization of Economic Education in the "Margo Tani" Watermelon Farmer Group in the village of Wotgalih brought the price of rent and the selling price of land to rise. The income of the watermelon farmers has increased and is living a prosperous life and the local village is well-built and neat.Abstrak: Penelitian deskriptif kualitatif digunakan untuk proses internalisasi petani palawija ke petani semangka yang ada di desa Wotgalih kecamatan Yosowilangun kabupaten Lumajang. Berdasarkan fenomena yang ada, dampak yang muncul akibat proses internalisasi dapat dilihat dari ranah pendidikan ekonomi, khususnya pendidikan non formal. Data dan sumber data dikumpulkan berdasarkan observasi dan wawancara terhadap beberapa informan yang tinggal di wilayah Wotgalih Yosowilangun. Hasil analisis data yang terkumpul dari pengurus dan anggota kelompok Margo Tani ada dua, yaitu proses internalisasi terhadap petani palawija dan petani semangka sama-sama melalui tiga hal yaitu belajar sambil bekerja, belajar dari mulut ke mulut dan belajar sambil praktik. Bedanya adalah diantara ketiganya pada petani palawija yaitu pofesi petani palawija ada yang diperoleh secara turun temurun dari pihak keluarga. Berbeda dengan bertani buah semangka yang diperoleh melalui tiga hal tersebut tanpa harus mengeluarkan biaya pribadi. Kedua, Dampak Internalisasi Pendidikan Ekonomi Pada Kelompok Petani Semangka “Margo Tani” di desa Wotgalih membawa harga sewa dan nilai jual lahan tanah naik. Pendapatan masyarakat petani semangka meningkat dan hidup sejahtera dan desa setempat terbangun serta tertata rapi.